1994
DOI: 10.1002/ajh.2830470410
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction with three nucleoside analogs on freshly isolated B‐chronic lymphocytic leukemia cells

Abstract: The cytotoxic effects and the induction of programmed cell death (apoptosis) by Fludarabine (FLU), 2-chlorodeoxyadenosine (2-CdA), and deoxycoformycin (DCF) with/without alpha-interferon (alpha-IFN) were evaluated in vitro against freshly isolated B-chronic lymphocytic leukemia (B-CLL) cells. Cytotoxicity was evaluated according to the soluble tetrazolium/formazan assay. Regarding the cytotoxicity, FLU, 2-CdA, and DCF showed a mean antitumor activity of 45% +/- 3.39 (mean +/- S.D.), 55% +/- 4.72, and 20% +/- 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…This occurs both spontaneously (Collins et al, 1989), suggesting that the culture systems lack a cytokine that in vivo ensures survival (Mainou-Fowler et al, 1996), or upon exposure to glucocorticoid hormones (McConkey et al, 1991) or drugs used clinically such as fludarabine (9-b-D-arabinofuranosyl-2-fluoradenine, F-ara-A), a purine nucleoside analogue resistant to adenosine deaminase Zinzani et al, 1994;McConkey et al, 1996). F-ara-A is of great interest because of its strong therapeutic activity in low-grade lymphoid malignancies (Keating et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs both spontaneously (Collins et al, 1989), suggesting that the culture systems lack a cytokine that in vivo ensures survival (Mainou-Fowler et al, 1996), or upon exposure to glucocorticoid hormones (McConkey et al, 1991) or drugs used clinically such as fludarabine (9-b-D-arabinofuranosyl-2-fluoradenine, F-ara-A), a purine nucleoside analogue resistant to adenosine deaminase Zinzani et al, 1994;McConkey et al, 1996). F-ara-A is of great interest because of its strong therapeutic activity in low-grade lymphoid malignancies (Keating et al, 1989).…”
mentioning
confidence: 99%
“…F-ara-A is of great interest because of its strong therapeutic activity in low-grade lymphoid malignancies (Keating et al, 1989). Though F-ara-A is a potent inducer of apoptosis in CLL cell Zinzani et al, 1994;McConkey et al, 1996), the precise molecular mechanism through which it exerts this effect has not yet been fully established (Robertson et al, 1992;Miyashita & Reed, 1992Menzel et al, 1996). Recently, it has been reported that apoptosis sensitivity in CLL cells is determined by endogenous endonuclease content and by the relative expression of Bcl-2 and Bax (McConkey et al, 1996;Petersen et al, 1996;Thomas et al, 1996).…”
mentioning
confidence: 99%
“…3 Several in vitro studies indicate that in CLL cells fludarabine induces apoptosis, suggesting that programmed cell death is the mechanism of their therapeutic action. [4][5][6][7][8][9] As CLL cells are predominantly quiescent cells, the proapoptotic activity of fludarabine could be due to inhibition of RNA synthesis or alteration of DNA repair. Both p53-dependent and -independent mechanisms have been described.…”
Section: Introductionmentioning
confidence: 99%
“…18 Experimental evidence indicates that in CLL cells most of these drugs induce apoptosis ex vivo, suggesting that programmed cell death is the mechanism of their therapeutic action. 11,14,[19][20][21][22] Thus, in response to apoptotic signals, cytochrome c is released from mitochondria and binds to the adaptor protein Apaf-1. This results in the activation of caspase-9, which triggers downstream caspases, such as caspase-3.…”
mentioning
confidence: 99%